Hepatoprotective effect of 2′-O-galloylhyperin against oxidative stress-induced liver damage through induction of Nrf2/ARE-mediated antioxidant pathway. (April 2017) - Wang, Peng; Gao, Yi-Meng; Sun, Xing; Guo, Na; Li, Ji; Wang, Wei; Yao, Li-Ping; Fu, Yu-Jie
Abstract: 2′- O -galloylhyperin (2′- O -GH), an active compound isolated from Pyrola calliantha, possesses remarkable antioxidant activity. The aims of this study were to investigate the hepatoprotective effect of 2′- O -GH against oxidative stress and elucidate the underlying mechanistic signaling pathways in HepG2 cells as well as in an animal model. Results showed that 2′- O -GH significantly inhibited hydrogen peroxide (H2 O2 )-induced HepG2 cell death in a dose dependent manner. The mitogen-activated protein kinase activation, ROS production, mitochondrial membrane potential, intracellular calcium level and subsequent apoptotic protein activation in H2 O2 -stimulated HepG2 cells were remarkably inhibited by 2′- O -GH. Furthermore, 2′- O -GH stimulation resulted in a fast and dramatic activation of Akt and nuclear translocation of the NF-E2-related factor 2 (Nrf2), along with the increased expression of heme oxygenase-1 (HO-1) and levels of glutathione (GSH). Meanwhile, histopathological evaluation of the liver also revealed that 2′- O -GH effectively ameliorated CCl4 -induced the hepatic damage by reducing alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities. Therefore, these results suggested the hepatoprotective effect of 2′-O-GH might be correlated with its antioxidant and free radical scavenger effect. Graphical abstract: Highlights: 2′- O -galloylhyperin prevented CCl4 -induced liver injury. 2′- O -galloylhyperin protects against H2 O2 -induced cell death via inhibition of ROS generation and cellular apoptosis. 2′- O -galloylhyperin inhibited H2 O2 -induced MAPK activation. AKT activation mediates 2′- O -galloylhyperin induced Nrf2/HO-1 activation and cytoprotection.